Reforming motor accident compensation scheme: a no-fault liability option for Malaysia - Nicholson, Charles; Amin, Naemah (LexisNexis, 2013)
A no fault compensation scheme, as an alternative compensatory model, made its appearance as a consequence of the failure of the tort system to adequately compensate accident victims. The scheme provided an entirely new dimension to the civil justice system in dealing with the plight of accident victims by replacing the traditional notion of individual liability with a pragmatic concept based on the responsibility of the community as a whole. Some of these new schemes operated as complementary to the existing tort law. While others involved tort law being completely replaced by the new compensation schemes. In support of the proposal for introduction of such a scheme in Malaysia, this article aims to discuss a preferable no-fault liability option for this country which is the hybrid or modified no-fault compensation scheme.